Cooperation for innovation in services: learning from consultancy in Portugal - Fernandes, Silvia (2019)
This study addresses the effects of different sources on types of innovation introduced by the Portuguese consultancy firms. It distinguishes the most influent factors in product, process, organisational and marketing innovations. The assessment framework incorporated three steps: 1) evaluating the propensity to use information sources and cooperate with external agents; 2) identifying the sources used most often during innovation; 3) deriving profiles of the sampled firms. The underlying methodology consisted of logistic regressions which have identified predictors and emphasised disparities concerning the use of internal/external sources and agents. Results suggest the potential of complementing internal sources with external knowledge for innovation purposes. Due to the economic crisis, investments tend to postpone product/service innovation type. Nevertheless, effective innovation drivers can come from customers, as sources for more tailored products/services, and from certain processes that can contribute to firms' integration and internationalisation.